2013
DOI: 10.1063/1.4803710
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements in the lightning impulse breakdown characteristics of natural ester dielectric liquids

Abstract: In this letter, we experimentally demonstrate that the lightning impulse breakdown characteristics of natural ester liquids can be significantly enhanced by dispersing molecular additives possessing lower values of both the ionization potential and 1st excitation energies as compared to the base liquid. One such additive contributed to an increase in the breakdown and acceleration voltage of the base liquid by 32% and 90%, respectively. Apart from the expected influence of the low ionization potential of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 11 publications
2
40
1
Order By: Relevance
“…However, in this experiment it has an effect similar to but weaker than with DMA, and this experiment alone cannot tell if the effect is caused by the low excitation level or the ionization potential which is lower than in the base liquid but still higher than in DMA. That the effect is weaker than in DMA, which has a lowest excitation level almost twice as high as azobenzene, might indicate that it is not the excitation level which is important, but this is contrary to the discussion in a paper about a long gap experiment with a natural ester as base liquid [19].…”
Section: Acceleration Voltage Vs Additive Mole Fractioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, in this experiment it has an effect similar to but weaker than with DMA, and this experiment alone cannot tell if the effect is caused by the low excitation level or the ionization potential which is lower than in the base liquid but still higher than in DMA. That the effect is weaker than in DMA, which has a lowest excitation level almost twice as high as azobenzene, might indicate that it is not the excitation level which is important, but this is contrary to the discussion in a paper about a long gap experiment with a natural ester as base liquid [19].…”
Section: Acceleration Voltage Vs Additive Mole Fractioncontrasting
confidence: 53%
“…Azobenzene was included as an additive because of a hypothesis that the lowest electronic excitation level might have an influence [11,12,19], particularly at the higher local fields which may exist in front of a streamer tip, since the ionisation potential may be so reduced with increased field [10,11] that it approaches the lowest excitation level. However, in this experiment it has an effect similar to but weaker than with DMA, and this experiment alone cannot tell if the effect is caused by the low excitation level or the ionization potential which is lower than in the base liquid but still higher than in DMA.…”
Section: Acceleration Voltage Vs Additive Mole Fractionmentioning
confidence: 99%
“…4,5 Much work has been done to explore the effective way to inhibit the development of positive streamers in transformer oil with an attempt to improve its dielectric strength. 6,7 Fe 3 O 4 nanoparticles with unique electrical and physical properties have shown a great potential in improving breakdown strength of transformer oil. It was found that the positive impulse breakdown voltage of transformer oil can be increased by 82.6% by adding a proper concentration of Fe 3 O 4 nanoparticles.…”
mentioning
confidence: 99%
“…Photoionization and excitation is also essential in the streamer breakdown mechanism. It has been shown that additives with low-ionization potential and excitation energies in mineral oil can increase branching of streamers leading to decreased electrical field in the streamer and reduced speed of the propagation at specific voltages [4].…”
Section: Ionization and Excitationmentioning
confidence: 99%